Analysis of the Determining Factors of Generation Z's Interest in Working in the Agricultural Sector in Bima Regency - Awaludin, Muhammad; Maryam, ST; Fadliyanti, Luluk (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2024)
This research is motivated by the phenomenon of the high interest of generation Z in Bima Regency in choosing to work in the agricultural sector. This research aims to analyze the influence of various factors, such as family economic conditions, environment, personality, motivation, and farming experience, on Generation Z's interest in choosing to work in the agricultural sector in the Bima Regency area. The type of research used is quantitative-descriptive. The population is generation Z, aged 15